NOPCHAP1 is a PAQosome cofactor that helps loading NOP58 on RUVBL1/2 during box C/D snoRNP biogenesis. Issue 2 (24th December 2020) - Abel, Yoann; Paiva, Ana C F; Bizarro, Jonathan; Chagot, Marie-Eve; Santo, Paulo E; Robert, Marie-Cécile; Quinternet, Marc; Vandermoere, Franck; Sousa, Pedro M F; Fort, Philippe; Charpentier, Bruno; Manival, Xavier; et al.
Abstract: The PAQosome is a large complex composed of the HSP90/R2TP chaperone and a prefoldin-like module. It promotes the biogenesis of cellular machineries but it is unclear how it discriminates closely related client proteins. Among the main PAQosome clients are C/D snoRNPs and in particular their core protein NOP58. Using NOP58 mutants and proteomic experiments, we identify different assembly intermediates and show that C12ORF45, which we rename NOPCHAP1, acts as a bridge between NOP58 and PAQosome. NOPCHAP1 makes direct physical interactions with the CC-NOP domain of NOP58 and domain II of RUVBL1/2 AAA+ ATPases. Interestingly, NOPCHAP1 interaction with RUVBL1/2 is disrupted upon ATP binding. Moreover, while it robustly binds both yeast and human NOP58, it makes little interactions with NOP56 and PRPF31, two other closely related CC-NOP proteins. Expression of NOP58, but not NOP56 or PRPF31, is decreased in NOPCHAP1 KO cells. We propose that NOPCHAP1 is a client-loading PAQosome cofactor that selects NOP58 to promote box C/D snoRNP assembly.